IMF Staff Papers, Volume 47, Special Issue, IMF Annual Research Conference - Flood, Robert; Borensztein, Eduardo (Washington, D.C. : International Monetary Fund, 2001)
This paper presents a broad overview of postwar analytical thinking on international macroeconomics, culminating in a more detailed discussion of recent progress. The paper reviews important empirical evidence that has inspired alternative modeling approaches, as well as theoretical and policy considerations behind developments in the field. The paper presents an empirical study of fiscal policy in countries with extreme monetary regimes. It also examines members of multilateral currency unions, dollarized countries that officially use the money of another country, and countries using currency boards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet